Transcatheter aortic valve implantation in patients with and without concomitant coronary artery disease: comparison of characteristics and early outcome in the German multicenter TAVI registry - Abdel-Wahab, Mohamed S.; Horack, Martin; Senges, Jochen (Clinical research in cardiology, 2012)
ObjectiveTo examine the prevalence and impact of concomitant coronary artery disease (CAD) on short-term outcome after transcatheter aortic valve implantation (TAVI).BackgroundThe prevalence of CAD in patients undergoing surgical aortic valve replacement is estimated at 30-50 % and its presence increases procedural risk. The prevalence and impact of CAD on outcome after TAVI are not well defined.MethodsWe analyzed 1,382 patients enrolled in the German TAVI registry; the majority (81 %) received the Medtronic CoreValve. The presence of coronary lesions with ≥50 % stenosis on pre-TAVI angiography defined the existence of concomitant CAD.Results859 patients (62.2 %) had concomitant CAD, of which 534 (62.3 %) had multi-vessel and 83 (9.7 %) left main disease. Patients with CAD were younger (81.5 ± 6.1 vs. 82.1 ± 6.3 years, p < 0.05), more commonly males (49.4 vs. 30.0 %, p < 0.0001) and diabetics (36.9 vs. 31.2 %, p < 0.05), and had a worse Canadian Cardiovascular Society angina class at baseline compared to patients with no CAD. During TAVI patients with CAD more often required additional coronary intervention and had longer procedures, but procedural success rates were similar (97.1 vs. 97.7 %). Crude in-hospital mortality was higher in patients with CAD (10.0 vs. 5.5 %, OR 1.90, 95 % CI 1.23-2.93), but this was not significant after adjustment for confounders (adjusted OR 1.41, 95 % CI 0.85-2.33). Both groups had significant improvement in 30-day symptoms and quality of life.ConclusionThe prevalence of CAD in contemporary TAVI patients is high. Its presence characterizes a high-risk population and is associated with increased crude short-term mortality, largely explained by co-morbidities, but does not limit functional improvement after TAVI.
Gesehen am 04.12.2018